The highlands of Colombia's Cauca Valley Department (2000)
This work, beautifully illustrated, sumarizes the research carried out by the CVC, together with a long list of scientist from a host of national and international institutions. It is hoped that this work, intended for the general public but especially for those whose home is the Cauca Valley, will create a heightened awareness of this unique region and perhaps sway many more individuals to rise to its defense and conservation.